2015
DOI: 10.1177/0044118x15617400
|View full text |Cite
|
Sign up to set email alerts
|

Alone on the Inside: The Impact of Social Isolation and Helping Others on AOD Use and Criminal Activity

Abstract: Because addiction is a socially isolating disease, social support for recovery is an important element of treatment planning. This study examines the relationship between social isolation, giving and receiving social support in Alcoholics Anonymous during treatment, and post-treatment outcomes among juvenile offenders court-referred to addiction treatment. Adolescents (N = 195) aged 14 to 18 years were prospectively assessed at treatment admission, treatment discharge, 6 months, and 12 months after treatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
2
32
0
1
Order By: Relevance
“…Evidence-based studies have found that youths who are spiritually active, participate in a faith community, and invest in a prayerful relationship with their God are less likely to use or abuse drugs and alcohol and engage in related criminal activity (Johnson et al 2015, 2016a, b; Lee et al 2014, 2017; Post et al 2015, 2016). A seminal 2-year study by The National Center on Addiction and Substance Abuse (2001) at Columbia University, directed by Joseph A. Califano Jr., the former US Secretary of Health, Education, and Welfare in the Clinton administration, found that the teens who did not consider religious beliefs important were almost three times more likely to smoke, five times more likely to binge on alcohol, and almost eight times more likely to use marijuana compared with the teens who strongly appreciated the significance of religion in their daily lives.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…Evidence-based studies have found that youths who are spiritually active, participate in a faith community, and invest in a prayerful relationship with their God are less likely to use or abuse drugs and alcohol and engage in related criminal activity (Johnson et al 2015, 2016a, b; Lee et al 2014, 2017; Post et al 2015, 2016). A seminal 2-year study by The National Center on Addiction and Substance Abuse (2001) at Columbia University, directed by Joseph A. Califano Jr., the former US Secretary of Health, Education, and Welfare in the Clinton administration, found that the teens who did not consider religious beliefs important were almost three times more likely to smoke, five times more likely to binge on alcohol, and almost eight times more likely to use marijuana compared with the teens who strongly appreciated the significance of religion in their daily lives.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…The effect on providers’ own physical activity behavior is in line with findings from a previous diary study in the context of smoking cessation, demonstrating that in both male and female romantic partners, providing more smoking-specific support on a given day related to less self-reported cigarettes smoked that day ( Lüscher et al, 2017 ). Other studies investigating this association in the context of alcohol and substance use with a between-person focus ( Lüscher and Scholz, 2017 ), across larger time intervals as well as outside the romantic relationship ( Johnson et al, 2018 ; e.g., Liu et al, 2020 ) resulted in rather mixed evidence.…”
Section: Discussionmentioning
confidence: 99%
“…So far, a few studies exist that investigated the effects of providing social support on health behavior in the context of substance use, with mixed results. Giving help to other juveniles, as opposed to receiving help, significantly reduced the risk of relapse in alcohol and other drug use during 12 months following an addiction treatment ( Johnson et al, 2018 ). A main effect of providing support through online social support groups on alcohol and drug use 6 and 12 months later was, however, not confirmed ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, music may intensify PAS use through the exposure to lyrics that encourage it [52] or through the repeated participation to concerts or festive events [83,101,102,109]. The social mechanisms underlying music involvement also play a role since some individuals replace social support with music, which may lead to isolation, a factor known to increase the severity of PAS use [55,121,122]. On the other hand, music promotes recovery and abstinence in individuals with a former problematic PAS use.…”
Section: Resultsmentioning
confidence: 99%